A Review Article of the Pragmatics-Based-Curriculum in EFL Context: Focus on the Curriculum in Iraq - Ahmed Ibrahim; Mahendran Maniam (BIRCU, 2020)
The benefit of studying language through pragmatics is that the people can realize the other’s meaning and the important disadvantage is that analyzing the peoples’ concepts is hard objectively. The study of pragmatics is interesting as it studies how people make sense of each other linguistically, in the same time, it can be a disappointed area of study because it needs us to make sense of people and what they have in mind. According to Bardovi-Harlig (1991), the real responsibility of the classroom teacher is making students more aware about existing pragmatic functions in language, especially in discourse. The teachers should know about these speech acts and their elements to use the natural input for the students in a particular content, for a particular purpose, and as part of a strategy. Accordingly, the current review article aims at revealing the following; first, is pragmatics important in teaching and learning a second and foreign languages, based on this, is it a part of teaching English? Second, to show to what extent pragmatics is included in the EFL curriculums, textbooks more specifically?